External Voting The Patterns and Drivers of Central European Migrants' Homeland Electoral Participation - Szulecki, Kacper; Erdal, Marta Bivand; Stanley, Ben (Migration, Diasporas and Citizenship, 2023)
XI, 116 p. 5 illus., 4 illus. in color.